CCNA Wireless 200-355 - Henry, Jerome (Engineer) (LiveLessons (Indianapolis, Ind.), 2015)
More than 21 hours of video training covering all of the objectives in the CCNA Wireless WIFUND 200-355 exam. The CCNA Wireless 200-355 Complete Video Course is a unique video product that provides users with more than 21 hours of personal, visual instruction from wireless expert and instructor Jerome Henry. Video lessons cover all objectives on the CCNA Wireless; WIFUND 200-355 exam. The unique video product contains a series of short instructional videos that demonstrates the process of designing, surveying, deploying, configuring, and troubleshooting Cisco Wi-Fi networks. The videos cover the full range of topics you need to understand Wi-Fi, manage a wireless network, and successfully prepare for the CCNA Wireless certification. CCNA Wireless 200-355 Complete Video Course contains 12 modules, subdivided into 50 lessons and 210 sub-lessons, for a total of more than 21 hours of instruction. The videos consist of audio instruction and animations. Each video presents detailed objectives and video captures. Audio instruction throughout offers detailed explanations and tips.